Proceedings of the 19th ACM Symposium on Virtual Reality Software and Technology 2013
DOI: 10.1145/2503713.2503738
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-enabled haptic-based serious game for post stroke rehabilitation

Abstract: In this paper, we propose and develop a novel adaptive haptic-based serious game for post stroke rehabilitation. Real-time patients emotions monitoring based on the Electroencephalogram (EEG) is used as an additional game control. A subject-dependent algorithm recognizing negative and positive emotions from EEG is integrated. Force feedback is proposed and implemented in the game. The proposed EEG-enabled haptic-based serious game could help to promote rehabilitation of the patients with motor deficits after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Numerous on and off-body sensors often become part of serious games. Hou and his colleagues claimed that an EEG-enabled haptic-based serious game might aid in the rehabilitation of stroke patients with motor deficiencies [65]. The findings of a study [66] that combined EMG and depth data revealed that the virtual reality (VR) environment presented here can improve muscle activation in elbow flexion-extension motions.…”
Section: Serious Games Targeting Stroke Rehabilitationmentioning
confidence: 82%
“…Numerous on and off-body sensors often become part of serious games. Hou and his colleagues claimed that an EEG-enabled haptic-based serious game might aid in the rehabilitation of stroke patients with motor deficiencies [65]. The findings of a study [66] that combined EMG and depth data revealed that the virtual reality (VR) environment presented here can improve muscle activation in elbow flexion-extension motions.…”
Section: Serious Games Targeting Stroke Rehabilitationmentioning
confidence: 82%
“…In this case study, we explore the application of EEG recognition for detecting happiness in the context of virtual reality (VR) gaming [8]. The goal is to develop a system that adapts gameplay dynamically based on the player's emotional state, enhancing the gaming experience and promoting positive affect, Figure 3.…”
Section: Case Study: Eeg Recognition Of Happiness In Virtual Reality ...mentioning
confidence: 99%
“…These devices, specifically EEG-based devices, have also proved to be useful for making adaptive games [21], which is particularly our field of study. EEG biosensors, are suitable to be used for cognitive games [22]; in multiplayer cooperative games [23], for evaluating how the cognitive activity changes while playing with teammates; also in serious games, in order to promote rehabilitation with patients that suffer from motor deficits due to a stroke, these researchers developed a new game that aims to help them with the process of rehabilitation [24].…”
Section: Related Workmentioning
confidence: 99%